Positive and Negative Aspects of Copaxone ( Glatiramer acetate) Action on TC, TG HbA1c and Iron Levels in The Sera of Iraqi Women with Multiple Sclerosis in Baghdad (Baghdad Science Journal, 2017)
The aim of the present study is to highlight the role of total cholesterol (TC), triacylglycerol (TG), Glycated hemoglobin A1c and iron in Iraqi women with multiple sclerosis and also to examine the biochemical action of copaxone (which is the most widely used in the 21st century to treat multiple sclerosis) on these biochemical parameters. This is the first study in Iraq which deals copaxone action on TC , TG , HbA1c and iron. Ninety women in their fourth decade suffering from multiple sclerosis were enrolled in this study. They were divided into: the first (group B) composed of (30) women without any treatment related to multiple sclerosis or any treatment linked with chronic or inflammatory diseases. The second (group A1) included (30) women under treatment with copaxone for 1 year, whereas the third group (group A2) involved (30) women under treatment with copaxone for 2 years. Patients groups were compared with a healthy control group (group C) composed of (30) healthy women, TC, TG, HbA1c and iron levels were determined in the sera of patients and control groups. Results of the present study has revealed that TC was high significantly increasing in the sera of group B (250.68±9.76) mg/dl compared with group C (175.36±8.81) mg/dl, while it was high significantly decreasing in the sera of groups A1 (211.88±5.90) mg/dl and A2 (212.12±5.60) mg/dL compared with group B (250.68±9.76) mg/dl. Beside, a non-significant difference was suggested between groups A1 (211.88±5.90) mg/dl and A2 (212.12±5.60) mg/dl. The present study also reported that TG was high significantly increasing in group B (224.84±10.76) mg / dl compared with group C (131.36±7.53) mg/dL whereas a significant decrease was shown in group A1(142.48±4.63) mg/dl and group A2 (195±4.20) mg/dl compared with group B (224.84±10.76) mg / dl. Surprisingly, a highly significant increase was reported in group A2 (195±4.20) mg/dl compared with group A1(142.48±4.63) mg/dl. The present study also suggested that HbA1c level was high significantly increasing in the sera of group B (6.53±0.57) mg/dl compared with group C (4.99±0.07) mg/dl. Oppositely, it was high significantly decreasing in the sera of groups A1 (4.72±0.42) mg/dl and A2 (4.53±0.35) mg/dl compared with group B (6.53±0.57) mg/dl. Futhermore, a non-significant difference was noted between groups A1 (4.72±0.42) mg/dl and A2 (4.53±0.35) mg/dl. This study also reported that iron level was high significantly decreasing in the sera of group B (37.31±4.24) µg / dl compared with group C (98.23±9.21) µg/ dl, whereas it was significantly increasing in the sera of groups A1 (44.05±6.32) µg/dl and A2 (45.31±6.82) µg/dl compared with group B (37.31±4.24) µg/dl . A non significant difference was shown between groups A1 (44.05±6.32) µg / dl and A2 (45.31±6.82) µg / dl.